Donor Oocyte Conception and Pregnancy Complications: A Systematic Review and Meta-analysis. Issue 2 (June 2017) - Jeve, Y.B.; Potdar, N.; Opoku, A.; Khare, M.
Abstract : ( BJOG . 2016;123(9):1471–1480) The demand for donor oocyte (DO) conception has increased along with the growing trend of delayed childbirth. However, increased risk of complications such as pregnancy-induced hypertension (PIH) and preeclampsia have been reported in DO pregnancies irrespective of maternal age. Studies have found rates of hypertensive disorders of pregnancy as high as 16% to 40% in women with pregnancies conceived via DO. This systematic review and meta-analysis was undertaken to examine the obstetric outcomes of DO pregnancies compared with autologous-oocyte in vitro fertilization (IVF) pregnancies, and to determine if DO pregnancy is an independent risk factor for pregnancy-related complications.